Structural characteristics, lead isotopes of gold mineralizations of the border Huaytará- Tantará-Huancavelica (Perú) - Quispe Cangana, Jorge Luis (2006)
The Huaytará-Tantará belt extends along the western flank of the Western Cordillera of the Andes of central Peru. It contains Au-Ag (Pb-Zn-Cu) mineralizations hosted by volcanic sequences from Eocene to Miocene. It is affected by at least six phases of deformation, defined through structural analysis in four work stations: Antapite, Jatun Orcco, Pampa Andino and Castrovirreyna. The diagrams of lead evolution of 17 samples extracted of the three first, indicate hydrothermal processes independent, with a lead evolution similar in Pampa Andino and Jatun Orcco, but different to Antapite. Also, in Antapite the source of radiogenic lead proceed of an orogenic area, with prevalence both the upper crust and the lower crust, contrary to the others zones, that only show influence of the upper crust. Then it is considered that the magmatism of Antapite was deeper and that its fluids had more possibilities of leaching metals from the source. On the other hand, it is considered that the volcanism of the late Eocene related with the Pampa Andino caldera, does not have any relationship with the mineralization of this ore deposit.